Effects of dietary nutmeg (Myristica fragrans) seed meals on growth, non-specific immune indices, antioxidant status, gene expression analysis, and cold stress tolerance in zebrafish (Danio rerio) - Vakili, Farzaneh; Roosta, Zahra; Safari, Roghieh; Raeisi, Mojtaba; Hossain, Md. Sakhawat; Guerreiro, Inês; Akbarzadeh, Arash; Hoseinifar, Seyed Hossein (Frontiers in Nutrition, 2023)
A medicinal plant, Myristica fragrans seed meal (nutmeg), was utilized to evaluate its impact on growth, immunity and antioxidant defense of zebrafish (Danio rerio). In this regard, zebrafish (0.47 ± 0.04 g) (mean ± S.D.) were fed with 0% (control), 1% (T1-nutmeg), 2% (T2-nutmeg), and 3% (T3-nutmeg) of powdered nutmeg for 70 days. At the end of the feeding trial, growth performance, survival rate of fish and temperature-challenge effects were recorded. Immune and antioxidant parameters were also assessed through the collection of serum and skin mucus samples. The results indicated that nutmeg supplementation did not significantly influence growth of zebrafish (P > 0.05), however, survival rate of fish fed 2 and 3% of nutmeg supplementation significantly decreased (P < 0.05). The skin mucus and serum total protein, total immunoglobulin (Ig), and lysozyme activity were significantly increased in T3-nutmeg treatment in comparison to control (P < 0.05). Superoxide dismutase (SOD) and catalase (CAT) activities were also enhanced in T3-nutmeg group (P < 0.05). Nutmeg supplementation significantly upregulated the mRNA expression of growth hormone (gh) and insulin growth factor-1 (igf-1). Moreover, the nutmeg inclusion upregulated the expression of interleukin-1β (IL-1β), lysozyme, sod, and cat. The dietary supplementation of nutmeg significantly increased resistance of zebrafish against cold-water shock and survivability afterwards (P < 0.05). In conclusion, the supplementation of 3% powdered nutmeg in zebrafish diets could be suggested as an effective immune-stimulator that improves antioxidant defense, and stress tolerance.